Hydrocarbon pneumonitis with abscess formation following diesel siphoning. Issue 6 (28th June 2022) - Rajpoot, Akhilesh; Sharma, Prakhar; Kumar, Arjun; Rathore, Suyash Singh
Abstract : A man in his early 40s presented with a 1-month history of fever after accidental diesel aspiration. He had received treatment with intravenous antibiotics, steroids and supportive care. Contrast-enhanced CT of the thorax revealed a right middle lobe lung abscess and bronchoscopy revealed hyperaemia around the middle lobe bronchus. The abscess was initially managed by drainage using a pigtail catheter and intravenous antibiotics. However, only partial drainage of the abscess was achieved and fever persisted. The cardiothoracic surgery team performed drainage of lung abscess through a right posterolateral thoracotomy. Postprocedure, the patient's symptoms improved and the patient was discharged in good health. This case demonstrates a rare complication of hydrocarbon aspiration pneumonitis and lung abscess. Post acute management of diesel aspiration, patients should be advised to return for medical assessment immediately, should symptoms like persistent fever and chest pain recur or persist as these symptoms may herald the development of post-hydrocarbon-aspiration lung abscess.